2010
DOI: 10.26719/2010.16.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal disorders among bank office workers in Kuwait

Abstract: This cross-sectional observational study assessed the pattern of musculoskeletal disorders (MSDs) suffered by bank office workers in Kuwait. A self-administered validated questionnaire was used that included the Nordic musculoskeletal questionnaire and 12-item general health questionnaire (GHQ12). Of 750 employees, 80% suffered at least 1 episode of MSD during the previous year and 42% suffered at least 1 disabling episode. The most affected body parts were the neck (53.5%), lower back (51.1%), shoulders (49.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
93
3
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(131 citation statements)
references
References 10 publications
29
93
3
6
Order By: Relevance
“…Chubineh study showed prevalence of back and neck signs were 49% and 47%, respectively in office workers (8). Prevalence of developing disorders at least in one region of the body during previous 12 months and even in previous 7 days were reported by office workers, which were consistent with similar studies (4,15,19,20). In addition, results showed a significant relationship between job duration and age of individuals with musculoskeletal disorders in all studied body parts (P < 0.05), which other studies reported as significant factor too (21).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Chubineh study showed prevalence of back and neck signs were 49% and 47%, respectively in office workers (8). Prevalence of developing disorders at least in one region of the body during previous 12 months and even in previous 7 days were reported by office workers, which were consistent with similar studies (4,15,19,20). In addition, results showed a significant relationship between job duration and age of individuals with musculoskeletal disorders in all studied body parts (P < 0.05), which other studies reported as significant factor too (21).…”
Section: Discussionsupporting
confidence: 81%
“…Musculoskeletal disorders related to work are among health problems in work places of industrially developed and developing countries, which are caused by work cumulative trauma disorders (WCTDs) during exposure to stressful biomechanical and social-psychological agents in work places for a long period of time (3). Most causes of these disorders include long sitting and excessive leaning (4). According to researchers and in spite of increase in automatic and mechanized processes, occupational musculoskeletal disorders are still the major factor in losing work hours, increase of costs, and human damages (5).…”
Section: Introductionmentioning
confidence: 99%
“…In previous epidemiologic studies, it was reported that short resting breaks have positive effects (7,38,37). Use of screen is diminished together with short breaks, muscle load due to Ulutas Med J 2017;3(2):39-47 poor ergonomic conditions is decreased.…”
Section: Discussionmentioning
confidence: 99%
“…UE-WMSC prevalence in elbow region is found to be lower than what is repor-ted in previous studies, between 6.0%-30% (16). This situation could be explained by the joint structure of elbows, by use of handarm support and by the fact that degenerative diseases are less observed in this region.In a cross-sectional study carried out in Kuwait to determine existence of UE-WMSC for bank employees, prevalence of MSC is found to be 80% while the most affected parts of the body are neck (53.5%), waists (51,1%), shoulders (49.2%) and back (38.4%) (17). In Balcı's dissertation study covering the bank employees in Gaziantep Province, the prevalence of musculoskeletal complaints is determined as showed that the most common symptoms for women working in call centers are observed in neck (53%), which is followed by shoulders (42%) and hand-wrist area (30%) (19).…”
Section: Discussionmentioning
confidence: 99%
“…Among Hong Kong bankers, the prevalence of WMSDs in various body parts was reported as follows: neck-31.4%, back 30.6%, shoulder-16.5%, hand and wrist-14.9% and arm-6.6% [15]. A Kuwaiti study on musculoskeletal disorders among bank office workers reported that the most affected body parts were the neck (53.5%), lower back (51.1%), shoulders (49.2%) and upper back (38.4%) [16]. Lacerda et al [17] found a prevalence rate of 56.2% WMSDs among bank workers in Northeast Brazil.…”
Section: Introductionmentioning
confidence: 99%